Sistem Informasi Pengolahan Data Non Kurikuler Mahasiswa - HabibahSari, Nur, Husni Thamrin, S.T., M.T., Ph.D (2016)
Technology nowadays continues to grow. The author builds an Information Systems to Process Non-curricular Activities to facilitate students to know the information in academic achievement and the activity or activities of any Non-curricular followed by each student. The author designed the system using PHP and Mysql as database. Notepad++ and C56 Dreamwever as the primary software during construction. The method used is SDLC (System Development Life Cycle), which is a method that describes the life cycle of information systems development in the design of information systems. The author concludes that the use of information systems applications for non-curricular data processing this can facilitate the Faculty of Economics and Business to obtain information about the activities of any non-curricular followed by each student. Keywords: information systems, non-curricular, students